Sistem Penerimaan Peserta Didik Baru dengan Pemodelan System Development Life Cycle (SDLC) di SMA Negeri Lewa Tidahu - Hermanus Dara Taru; Yustina Rada; Hawu Yogia Pradana Uly (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
SMA Negeri Lewa Tidahu is one of the educational institutions that conducts the process of admitting new students, an annual activity that is still carried out manually. However, with the current development of digital media, nearly every group across various age levels requires fast internet connectivity. The issues faced include inefficient document management, frequent errors by prospective students in filling out manual registration forms, and unclear writing on the forms submitted to the school, making them difficult for operators to read. This results in inefficiency in terms of time and inaccuracies in data entry. Therefore, it is necessary to develop a new student admission system that allows students to access detailed information. This system is designed using the System Development Life Cycle (SDLC) model, which includes stages such as requirements analysis, design, programming, Black Box testing, SUS evaluation, and maintenance. The implementation of this new student admission system will simplify the process for users.